Analisis Efektivitas Sistem Pengendalian Internal Atas Persediaan Obat Pada Rumah Sakit Ibu dan Anak (RSIA) Permata Hati Mataram - Qais, Ahmad; Fitriyah, Nur (Jurnal Riset Mahasiswa Akuntansi, 2025)
The purpose of this study is to determine the application of elements of the internal control system for drug supplies at RSIA Permata Hati Mataram. Drug supplies are one of the important assets owned by RSIA Permata Hati Mataram. Because inventory is an asset, good internal control must be carried out to keep the inventory from things that may happen. To obtain the necessary data, use a quantitative approach method to find answers based on basic and causal factors by analyzing the causal factors of the occurrence of descriptive data. From the results of the study, it is concluded that the internal control of the supply of drugs at RSIA Permata Hati Mataram is effective, where there is a separation between functions related to the receipt and issuance of goods. As well as showing that the pharmaceutical management of RSIA Permata Hati Mataram has implemented elements of internal control, the organizational structure of the pharmacy of RSIA Permata Hati Mataram is designed and arranged functionally so that the duties and responsibilities of each part are clean, so that errors and irregularities in the implementation of the duties and responsibilities carried out by each can be detected.